Perceived causes and management of epilepsy among rural community dwellers in Ghana: a qualitative synthesis - Gyaase, Daniel; Gyaase, Theresah Ivy; Tawiah, Rebecca; Atta-Osei, Godfred; Owusu, Isaac; Mprah, Wisdom Kwadwo; Enuameh, Yeetey Akpe (Frontiers in Neurology, 2023)
Background In Ghana, over 270,000 people live with epilepsy, of which 70% do not receive treatment. Despite the high number of people with the condition, misconceptions exist about its causes and management in African regions. The study assessed the perceived causes and management of epilepsy among rural community dwellers in Ghana. Methods A qualitative approach and phenomenological design were employed for the study. The population comprised community dwellers in Berekum, a rural town in the Bono Region of Ghana. A convenience sampling technique was used to sample the participants. An in-depth face-to-face interview with a semi-structured interview guide was used to collect participant data. Data were analyzed using inductive thematic analysis. Result A total of 15 participants were interviewed in the study, after which saturation was reached. Seven of the participants were men, and eight were women. Two categories emerged as the causes of epilepsy: socio-cultural and superstitious causes and biomedical causes. The socio-cultural and superstitious causes include “a manifestation or an influence of an evil spirit,” “family curse or disease,” “punishment from ancestors or gods of the land,” “having several convulsions,” “exposure to foam from an epileptic,” and “bites from an epileptic during seizures”, while the biomedical causes are “brain damage,” “blood group,” and “genetic makeup”. Consulting with the spiritual realm, pouring water on the person or washing the person's face, and putting a spoon in the mouth were identified by the participants as ways to manage epilepsy. Conclusion The causes of epilepsy are primarily linked to the supernatural, with the results indicating that rural community residents largely attribute epilepsy to “evil spirits”. This implies that the rural communities' knowledge about the causes of epilepsy is based on the social causation theory of disease and disability, which relates diseases to the supernatural. Management of the condition was mainly seen as spiritual.